Brain organoids: A promising model to assess oxidative stress‐induced central nervous system damage. Issue 5 (18th May 2021) - Oyefeso, Foluwasomi A.; Muotri, Alysson R.; Wilson, Christopher G.; Pecaut, Michael J.
Abstract: Oxidative stress (OS) is one of the most significant propagators of systemic damage with implications for widespread pathologies such as vascular disease, accelerated aging, degenerative disease, inflammation, and traumatic injury. OS can be induced by numerous factors such as environmental conditions, lifestyle choices, disease states, and genetic susceptibility. It is tied to the accumulation of free radicals, mitochondrial dysfunction, and insufficient antioxidant protection, which leads to cell aging and tissue degeneration over time. Unregulated systemic increase in reactive species, which contain harmful free radicals, can lead to diverse tissue‐specific OS responses and disease. Studies of OS in the brain, for example, have demonstrated how this state contributes to neurodegeneration and altered neural plasticity. As the worldwide life expectancy has increased over the last few decades, the prevalence of OS‐related diseases resulting from age‐associated progressive tissue degeneration. Unfortunately, vital translational research studies designed to identify and target disease biomarkers in human patients have been impeded by many factors (e.g., limited access to human brain tissue for research purposes and poor translation of experimental models). In recent years, stem cell–derived three‐dimensional tissue cultures known as "brain organoids" have taken the spotlight as a novel model for studying central nervous system (CNS) diseases. In this review, we discuss the potential of brain organoids to model the responses of human neural cells to OS, noting current and prospective limitations. Overall, brain organoids show promise as an innovative translational model to study CNS susceptibility to OS and elucidate the pathophysiology of the aging brain.